Pembelajaran Kitab Kuning dengan Menggunakan Kitab Al-Iktisyâf di Pondok Pesantren Puncak Darussalam Potoan Daya Palengaan Pamekasan - Mukriadi, Mukriadi; Gaffar, Abdul; Zainullah, Zainullah (Al-Lubab : Jurnal Penelitian Pendidikan dan Keagamaan Islam, 2022)
This article is motivated by the author's interest in the al-Iktisyâf learning system at the Puncak Darussalam Islamic boarding school, because learning the yellow book does not take long. In general, the santri in mastering the yellow book takes a minimum of 8 years, through the al-Iktisyâf book it can be reached in only 6 months. This article describes two aspects. First, the teaching materials in the al-Iktisyaf book are in the form of a learning guide consisting of two volumes of books and the arguments based on the Emriti book and the practice is in the form of the Taqrib book. The learning methods used in the Puncak Darus Salam Islamic boarding school are group methods, lectures, memorization, question and answer, bandongan and wetonan methods. Second, the inhibiting factors for learning the al-Iktisyâf book are the lack of interest of students in learning the yellow book, students do not feel at home in the cottage, the difficulty of creating a pleasant learning atmosphere and the existence of translated books. The supporting factors are the sincerity and readiness of the supervisor, the patience and sincerity of all the mentors. Keywords: Learning system, Kitab kuning, Kitab al-Iktisyâf